Quantitative and qualitative evaluation of sural nerve graft donor site - Ng, S.S.; Kwan, M.K.; Ahmad, Tunku Sara (Malaysian Medical Association, 2006)
This study is designed to evaluate twenty patients after sural nerve harvest using the single longitudinal incision method. The area of sensory loss to pin prick was assessed by the authors at different intervals. Donor site factors, scar cosmesis, functional status and complications were assessed using a questionnaire. The mean area of anaesthesia at one month was 65 cm2 and it had reduced by 77% to 15 cm2 at one and a half years. The mean area of reduced sensation was 49 cm2 at one month and it increased by 18% to 58 cm2 over the same period. Therefore, the total area of sensory deficit was reduced by 36% from 114 cm2 at one month to 73 cm2 at one and a half years. Subjective patient evaluation indicated moderate level of pain during immediate post surgical period, which reduced significantly at one month. A low level of neuroma symptoms was recorded throughout the study period. At a mean follow-up period of two years, there was no area of anaesthesia in 50% of the patients. Mean area of anaesthesia for all patients was 12 cm2 and mean area of reduced sensation was 55 cm2. Subjective patient evaluation indicated a low level of pain, neuroma symptoms and numbness over the sural nerve sensory distribution. Twenty five percent of the patients were not satisfied with the scar appearance. Function and daily activities were not affected significantly. No surgical complications were observed.